Impact of several matches in a day on physical performance in rugby sevens referees - Suarez-Arrones, L.; Nunez, J.; Munguia-Izquierdo, D.; Portillo, J.; Mendez-Villanueva, A. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To examine the effects of several matches per day on running performance and cardiovascular stress in referees during a national Rugby Sevens championship. Methods: Seven referees, who refereed 3 matches/ day, were monitored by GPS during 21 matches. Results: Referees` movement patterns were relatively stable from the 1st to the 2nd match, although a substantial decrease was observed in the 2nd match for maximal and average sprint distance. A substantial decrease in the number of sprints, maximal speed, walking, distance covered at medium intensity, total and >14 km/h distance covered per minute was observed in the 3rd match in comparison with the 2nd. Compared with the 1st match, in the 3rd game referees showed a substantial decrease in maximal and average sprint distance, total walking at medium intensity, distance covered >14 km/h, and high-intensity running distance. Referees exhibited a substantial decrease in average heart rate (HR), percentage of time at >70%HRmax, and percentage of time at >90%HRmax in the 2nd match compared with the 1st. Referees` HR responses were relatively stable from the 2nd to the 3rd match except for the HR zones of 71-80%HRmax and 81-90%HRmax and performance-efficiency index (Effindex). Substantial differences were observed in the 3rd match compared with the 1st in average HR, 81-90%HRmax, >90%HRmax, and Effindex. Conclusion: This study provides evidence of reduced overall running performance and pronounced reduction in high-intensity running performance during the last match in Rugby Sevens referees refereeing 3 matches in the same day.